The Impact of Mental Health on Breastfeeding Practices in Women of Color: A Cohort Study - Susan Gennaro; Bernadette Mazurek Melnyk; Zina Aghdasi; Caitlin M. O’Connor; Andrea Cooper; Melanie M. Aviles; Anne M. Gibeau; Laura A. Szalacha (Journal of Human Lactation, 2026)
Background: Breastfeeding intent and practices have not been well explicated in women of color, who are likely to experience perinatal anxiety, depression, or stress. Research Aim: The aim of this study was to examine factors influencing intent and infant feeding practices in pregnant people of color with heightened mental health conditions through 6 months postpartum. Method: As part of a larger longitudinal randomized control trial, 154 Black and/or Hispanic pregnant participants reported infant feeding intent at approximately 31 weeks’ gestation, and feeding practices at 6 weeks and 6 months postpartum. Hierarchical logistic regression models examined sociodemographic characteristics, Baby-Friendly designation, and antenatal mental health symptoms as predictors of breastfeeding at 6 weeks and 6 months postpartum. Results: In this study, compared to national statistics, intent to breastfeed and initiation rates respectively, were higher in Hispanic women (96.9% and 90.6%) than in Black women (91.1% and 94.1%). In multivariable models ( n = 147), maternal age was positively associated with breastfeeding at 6 weeks (aOR ≈ 1.10 per year). Delivery in a Baby-Friendly site was independently associated with higher odds of breastfeeding (aOR = 2.74–2.83 across models). Anxiety, depressive, and stress symptoms did not meaningfully attenuate this association, and none were independently associated with breastfeeding. Conclusion: With supportive breastfeeding practices, women can successfully initiate breastfeeding. Mothers experiencing increased anxiety, depression, or stress, breastfed, irrespective of their mental health. Nonetheless, breastfeeding decreased over time. Further research on community resources that can continue to support vulnerable women in their breastfeeding practices is needed.